2020
DOI: 10.1016/s2589-7500(20)30135-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of digital cognitive behavioural therapy for insomnia on insomnia severity: a large-scale randomised controlled trial

Abstract: Background Although several large-scale randomised controlled trials have shown the efficacy of digital cognitive behavioural therapy for insomnia (dCBT-I), there is a need to validate widespread dissemination of dCBT-I using recommended key outcomes for insomnia. We investigated the effect of a fully automated dCBT-I programme on insomnia severity, sleep-wake patterns, sleep medication use, and daytime impairment.Methods We did a parallel-group superiority randomised controlled trial comparing dCBT-I with onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 27 publications
7
81
0
Order By: Relevance
“…We extracted data for 1720 RCT participants as reported in the Intent to Treat analyses [ 23 ] (1 participant excluded due to corrupted data of the CSD). Completed CSD at baseline was 853 (Mean 11.0 days; SD = 0.71) for the SHUTi group and 867 (Mean 10.3 days; SD = 0.68) for the PE group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We extracted data for 1720 RCT participants as reported in the Intent to Treat analyses [ 23 ] (1 participant excluded due to corrupted data of the CSD). Completed CSD at baseline was 853 (Mean 11.0 days; SD = 0.71) for the SHUTi group and 867 (Mean 10.3 days; SD = 0.68) for the PE group.…”
Section: Resultsmentioning
confidence: 99%
“…The current study utilizes data from a recently published RCT [ 23 ] and the analyses reported were specified a priori in the trial protocol [ 24 ]. The RCT was pre-registered on the ClinicalTrials.gov website (NCT02558647).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second module employs "behavioral regulation" (a modified version of behavioral activation that emphasizes the importance of preventing over-stimulation or excessive activation in those at risk of hypo/mania), alongside sessions targeting sleep-wake cycle or circadian regulation (with techniques derived from CBT for insomnia) (16,17). Which interventions are initiated is determined by whether sleep disturbances are characterized by insomnia (which is often linked to arousal or anxiety), hypersomnia, unstable patterns, or prolonged sleep onset latency with late waking time (which may be a marker of circadian dysrhythmia) (17)(18)(19)(20).…”
Section: Interventionmentioning
confidence: 99%
“…2 Øystein Vedaa and colleagues' study in The Lancet Digital Health is an excellent addition to this evidence. 3 The study assessed the effectiveness of an automated dCBT-I intervention, Sleep Healthy Using the Internet (SHUTi), in a well conducted large-scale (n=1721) randomised controlled trial in Norway. The control group received online sleep education.…”
mentioning
confidence: 99%